The Use of Song as Learning Media in Teaching Listening to EFL Students - Rohana, Yogi; Saharani, Annisa Auliya (Indonesian Journal of Multidisciplinary Educational Research, 2023)
As one of fundamental receptive skill, listening skill is mostly neglected during the English language teaching learning process. The challenges on the process of teaching listening which may come from both the students or the teacher mostly become a problem that makes written mode of English language learning more dominant. The strategies on teaching listening skill might not be varied that causes the teaching learning process ineffective. This research is aimed to introduce the use of song in engaging students’ attention and creating fun teaching-learning process to increase the students’ achievement in listening skill. The research used quasi-experimental quantitative design. The number of sample used in this research is 72 students in the first grade of SMAN Gurah, Kediri. A test is used to collect the data of students’ achievement in listening. The test indicates the significant difference between the experimental group and control group as the researcher used the t test formula. From the result of data analysis, we find that the t-test is 2,53 at degree of freedom (df) 70 at 0,05 alpha (1,67). It means that the t-test is higher than the t-table (2,53>1,67). Thus, the hypothesis that teaching listening using song is improving students’ achievement on listening skill can be accepted.